A proposed integrated data collection, analysis and sharing platform for impact evaluation. (June 2016) - Kipf, Andreas; Brunette, Waylon; Kellerstrass, Jordan; Podolsky, Matthew; Rosa, Javier; Sundt, Mitchell; Wilson, Daniel; Borriello, Gaetano; Brewer, Eric; Thomas, Evan
Abstract: Global poverty reduction efforts value monitoring and evaluation, but often struggle to translate lessons learned from one intervention into practical application in another intervention. Commonly, data is not easily or often shared between interventions and summary data collected as part of an impact evaluation is often not available until after the intervention is complete. Equally limiting, the workflows that lead to research results are rarely published in a reproducible, reusable, and easy-to-understand fashion for others. Information and communication technologies widely used in commercial and government programs are growing in relevance for international global development professionals and offer a potential towards better data and workflow sharing. However, the technical and custom nature of many data management systems limits their accessibility to non-ICT professionals. The authors propose an end-to-end data collection, management, and dissemination platform designed for use by global development program managers and researchers. The system leverages smartphones, cellular based sensors, and cloud storage and computing to lower the entry barrier to impact evaluation.